Performance of the New FlashCam-based Camera in the 28 m Telescope of H.E.S.S. - Bi, Baiyang; Barcelo, Miquel; Bauer, Christian; Benkhali, Faical Ait; Catalano, Jacqueline; Diebold, Sebastian; Föhr, Christian; Funk, Stefan; Giavitto, Gianluca; Hermann, German; Hinton, Jim; Jung-Richardt, Ira; et al. (Proceedings of 37th International Cosmic Ray Conference — PoS(ICRC2021), 2022)
In October 2019, the central 28 m telescope of the H.E.S.S. experiment has been upgraded with a new camera. The camera is based on the FlashCam design which has been developed in view of a possible future implementation in the Medium-Sized Telescopes of the Cherenkov Telescope Array (CTA), with emphasis on cost and performance optimization and on reliability. The fully digital design of the trigger and readout system makes it possible to operate the camera at high event rates and to precisely adjust and understand the trigger system. The novel design of the frontend electronics achieves a dynamic range of over 3,000 photoelectrons with only one electronics readout circuit per pixel. Here we report on the performance parameters of the camera obtained during the first year of operation in the field, including operational stability and optimization of calibration algorithms.
CRIS-Team Scopus Importer:2024-12-16